Prevalência de recidiva em hanseníase : revisão sistemática e meta-análise - Silva, Fabiane Verônica da (2022)
The disease recurrence taxa is the main indicator of the efficacy of multidrug therapy. However, there is evidence of a reduction in the prevalence of disease since the implantation of multidrug therapy, its magnitude and high incapacitating power and its maintenance as a public health problem. Objective: To synthesize the scientific evidence related to the prevalence of relapse in leprosy after treatment with multidrug therapy. Method: a systematic review proposed according to the JBI Evidence Synthesis methodology for systematic reviews of prevalence studies, according to PRISMA-P, under registration number: CRD42020177141. The Menemonic PopCoCo (Population, Condition, Context) was adopted to determine the inclusion criteria. Population: individuals of both sexes and all ages, diagnosed as cases of leprosy in the paucibacillary and multibacillary forms and reported for recurrence. Condition: relapse of leprosy after multidrug therapy; Context: studies carried out within the scope of health services. The search strategy was carried out in the following databases: Pubmed/Mediline, LILACS; base; CINAHL; Scopus; WoS; EVIPnet; CARPHA. The Mendeley Reference Manager Software was used. The selection, methodological evaluation and data extraction steps were evaluated by two independent reviewers. When there was discrepancy, a third reviewer assessed. The random effects meta-analysis model was applied; heterogeneity between studies was analyzed using the Higgins test (I²) by means of the 95% confidence interval. Results: A total of 6,911 studies were found by the search strategies. After the selection steps of the studies, 29 records were included in the review. Of these, 24 are cohort studies, 2 are case-control studies and 3 are randomized clinical trials. In total, the review consisted of a population of 25,852 patients diagnosed with leprosy. Of these, 1,570 were cases of recurrence. It was found that of the total population that relapsed, 270 were investigated about sex, and of these 192 were male (12%). It was observed that 199 cases were analyzed in terms of age at recurrence (13%), of which 186 were 15 years of age 10 or older (93.5%). A higher prevalence of cases with multibacillary recurrence was observed (40.0%; n= 623) and, of the eight countries in which the studies were carried out, seven are countries with a high burden of leprosy, which includes India and Brazil. The meta-analysis of random effects among countries with the highest disease burden showed an overall prevalence of retreatment for relapse of 13% (95%CI: 0.11-0.15), with an overall prevalence of 65% in multibacillary cases (95%CI: 0.41-0.88). Conclusion: The evidence from this review demonstrates a high global prevalence of leprosy recurrence among the countries of India with 13% of cases (9%CI 0.06-0.20), followed by Brazil, with 16% (0.11-0 ,21), with higher prevalence among the multibacillary (65%).